Do Narcissists Self-Enhance? Disentangling the Associations Between Narcissism and Positive Versus Enhanced Self-Views Across Aspects of Narcissism, Content Domains, and Comparison Criteria. Issue 5 (July 2021) - Mielke, Ina; Humberg, Sarah; Leckelt, Marius; Geukes, Katharina; Back, Mitja D.
Across psychological disciplines, grandiose narcissism and self-enhancement have been treated as two closely related constructs. However, empirical research has not yielded conclusive insights about their association: It is currently unclear whether self-views of narcissistic individuals are more enhanced, in comparison with some criterion value, or whether their self-views are simply more positive than those of less narcissistic individuals. We aimed to clarify this fundamental issue with regard to (a) different aspects of narcissism (narcissistic admiration and rivalry), (b) different content domains of self-views (agency and communion), and (c) different criteria against which self-perceptions were compared (reputations, perceptions of others, and objective criteria). We used data from two multimethodological studies ( N = 420) and applied condition-based regression analyses, a statistical approach that is suitable for differentiating between self-enhancement and the mere positivity of self-views. Results contradicted general claims of narcissism as the "self-enhancer personality" and highlighted more specific patterns of narcissistic self-evaluations.